(3OjhGf GdGHdg GdHZOGOis - (3eMeO Hf HNJjGQ Hf YHO Gddg GdGHdg GdHZOGOj, GdGHdg GdHZOGOj,J (B579 (3g` s ((3Ydi Hf eMehO Hf CMeO GdebQi s)
(3ChdgG (B:s
(3bUjOI HOM HgG GdEeGe GdebJai dCeQ Gddg eMeO Hf GdEeGe GdeSJXgQ HCeQ Gdgd QGMJ dSQMg fYeGf hhGOjgG ZQ GdSMGFH JZOhgG ZhGOjgG s
(3BNQgG (B:s
(3CQHYI CHjGJ ai GHf GdLGPhQi HZG Gdba hGdYQS hGdchI QVh Hdi ai QGSg bhI BNQ eG hLO ef OjhGfg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B274s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI edi (B(387) s
Keywords: (3GdCOHs